"Volleyball" aneurysm of the posterior circumflex humeral artery - Bischoff, Moritz; Böckler, Dittmar; Geisbüsch, Philipp (Deutsches Ärzteblatt, 2021)
A 34-year-old male patient, a volleyball player, exhibited aneurysm embolization of the posterior circumflex humeral artery (PCHA; white asterisk). Since the patient initially presented with acute ischemia of the hand, surgical treatment by means of...
Gesehen am 16.06.2021